2013
DOI: 10.1371/journal.pone.0068897
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression of the CCAP Receptor in the Chagas’ Disease Vector, Rhodnius prolixus, and Its Involvement in Cardiac Control

Abstract: Rhodnius prolixus is the vector of Chagas’ disease, by virtue of transmitting the parasite Trypanosoma cruzi. There is no cure for Chagas’ disease and therefore controlling R. prolixus is currently the only method of prevention. Understanding the physiology of the disease vector is an important step in developing control measures. Crustacean cardioactive peptide (CCAP) is an important neuropeptide in insects because it has multiple physiological roles such as controlling heart rate and modulating ecdysis behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 44 publications
1
27
0
1
Order By: Relevance
“…D. melanogaster heartbeat frequency is increased during the last 10 h of adult development and peaks at 1 h before the ecdysis behavioral sequence in the white stage (Baker et al, 1999). Previously, we reported that RhoprCCAPR transcript level was up-regulated 10-fold in a pool of tissues containing the heart (dorsal vessel), trachea and fat body prior to ecdysis and dropped to basal levels post-ecdysis (Lee et al, 2013). This indicates that the heart/dorsal vessel may have increased sensitivity to CCAP during the ecdysis behavioral sequence.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…D. melanogaster heartbeat frequency is increased during the last 10 h of adult development and peaks at 1 h before the ecdysis behavioral sequence in the white stage (Baker et al, 1999). Previously, we reported that RhoprCCAPR transcript level was up-regulated 10-fold in a pool of tissues containing the heart (dorsal vessel), trachea and fat body prior to ecdysis and dropped to basal levels post-ecdysis (Lee et al, 2013). This indicates that the heart/dorsal vessel may have increased sensitivity to CCAP during the ecdysis behavioral sequence.…”
Section: Discussionmentioning
confidence: 96%
“…Tissues were dissected from R. prolixus 4th instar (Day 4–9 post-fed) and 5th instar (Day 1–6 post-ecdysis). Total RNA was isolated from tissues using the Trizol® reagent (Ambion, Austin, TX) and first-strand cDNA was synthesized using 100 ng of total RNA as previously described (Lee et al, 2013). The reaction was diluted 20-fold with nuclease free water and qPCR analyses were carried out on a CFX96Touch™ Real-Time PCR Detection System (Bio-Rad Laboratories Inc., Hercules, CA, USA) using the Ssofast™ EvaGreen supermix (Bio-Rad Laboratories Inc., Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations